Health literacy, perilaku bersih sehat, dan kesehatan balita: studi di wilayah tertinggal di Bengkulu, Sulawesi Selatan, dan Nusa Tenggara Timur - Prastuti Soewondo; Meliyanni Johar; Retno Pujisubekti; Halimah Halimah (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Health literacy, healthy and clean life styles, and under-five child’s health status: a study in remote areas in the provinces of Bengkulu, South Sulawesi, and East Nusa Tenggara Purpose: Health literacy is needed for people to make well-informed health decisions. This study assesses the role of health literacy on the practice of clean and healthy living at home, as well as on under-five children’s health. We focus on those living in left-behind areas, for whom preventive behaviours and staying healthy may be particularly important, as these areas often lack in health facilities.Methods: The survey was based on a sample of 4610 households, taken from 18 catchment areas of community health centers in three provinces of Bengkulu, South Sulawesi, and East Nusa Tenggara.Results: We find that health literacy is positively associated with many indicators of clean and healthy lifestyle, as well as young children’s healthz. Literacy about preventive measures increases the odds of handwashing before eating and preparing food, not spitting and covering nose/mouth when sneezing/coughing in public places, not smoking inside the house, and consuming vegetable-rich diet. Literacy about health insurance and health facilities associates positively with not spitting and covering nose/mouth when coughing/sneezing and good diet. Literacy about mother’s and child’s health in general have a positive association with young children’s outcomes.Conclusions: These results suggest that improving health literacy in rural and remote areas can lead to a sustainable health improvement that begins with the enactment of health-promoting habits at home and young children’s health.